2020
DOI: 10.18488/journal.61.2020.83.416.431
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Soft Skills Needs of Teacher Education Students

Abstract: The current study was undertaken to assess the soft skills needs of student teachers at Kuwait University, which led to the authors developing a two-part Likert-type questionnaire. The first part covered 49 soft skills categorized into five skills dimensions: employability, study, social, self-control, and problem-solving. The second part included five different approaches to acquiring soft skills. The results reveal that the medium-high level of need among the respondents for all 49 soft skills and their pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…ability to promote good interactions and intercommunication with their students, and among them. However, it has been found that teachers have an average level of sociability and empathy with their students [26]. Therefore, teachers feel a great need for training in the soft skills that are fundamental for developing their work in the classroom [27].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ability to promote good interactions and intercommunication with their students, and among them. However, it has been found that teachers have an average level of sociability and empathy with their students [26]. Therefore, teachers feel a great need for training in the soft skills that are fundamental for developing their work in the classroom [27].…”
Section: Methodsmentioning
confidence: 99%
“…Among the soft skills, the ability to stimulate critical thinking, creativity, and leadership are also highly valued [25] and, among others, are the ability to foster collaborative teamwork, the ability to promote good interactions and intercommunication with their students, and among them. However, it has been found that teachers have an average level of sociability and empathy with their students [26]. Therefore, teachers feel a great need for training in the soft skills that are fundamental for developing their work in the classroom [27].…”
Section: Introductionmentioning
confidence: 99%
“…Referring to the journal Quartile in SJR and/or JCR, the majority of the articles were published in Quartile 4 (AlHouli & Al-Khayatt, 2020;Elisa et al, 2020;Gendron, 2017;Hamilton, 2018;Noah & Aziz, 2020;Suprianto et al, 2018;Susilawati et al, 2020) and Quartile 2 (Abd Hamid et al, 2020;Hadiyanto et al 2017;Gero & Mano-Israeli, 2020;Rabaglietti et al 2021;Tang, 2020;Vourinen et al, 2021) journals; 4 articles were published in Quartile 3 (Harun & Salamuddin, 2013;Hendriana, 2017;Kniaz & Chukhno, 2021;Susilawati et al, 2021), and 2 articles in Quartile 1 journals (Iglesias-Pradas et al, 2015;Skura & Świderska, 2021). It must be noted that while the majority of the journals were indexed in Education, Psychology, and related areas (Special Need Education, Educational Psychology), 3 journals were indexed in the specific scientific area of teachers' expertise (in two cases Physics and in one case Applied Linguistics).…”
Section: Country Year Publication and Locus Of The Termmentioning
confidence: 99%
“…Eight articles focus on perceptions about the importance of SS and their development in teacher education programs. While the importance of SS is generally recognized and pre-service teachers tend to have a positive evaluation of their own SS (Hadiyanto et al 2017;Kniaz & Chukno, 2021), there are differences in opinion about the relative importance of concrete aspects of SS to the teacher profession (Hamilton, 2018;Tang, 2020), the contribution they make (Susilawati et al 2020) and in the evaluation of the teacher education programs regarding SS (AlHouli & Al-Khayatt, 2020;Kniaz & Chukno, 2021;Noah & Aziz, 2020). Factors such as knowledge area (Tang, 2020) and role (teacher and students; Gero & Mano-Israeli, 2020) seem to be important to understand these differences of opinion.…”
Section: Studying Teachers' Soft Skillsmentioning
confidence: 99%
“…There is a global shift in higher education to ensure graduates come out with necessary hard skills, as well as being readily employable. A number of the reviewed articles mentioned either national or global reference to competency, employability, or 21 st century skill standards (Abu Kasim et al, 2014;AlHouli & Al-Khayatt, 2020;Bastos et al, 2019;Bergh et al, 2006;Cham et al, 2020;Gonzalez et al, 2013;Jardim et al, 2020;Mailool et al, 2020;Maren et al, 2021;Meiners & Wisdom, 2020;Morrell et al, 2020;Ngang et al, 2015;Nor et al, 2011;Schutt et al, 2017;Sharma et al, 2021;Singh et al, 2017;Treem Guerin, 2014).…”
Section: Embedded Vs Stad-alone Coursesmentioning
confidence: 99%